DEVELOPMENT OF INORGANIC NANO FILLER REINFORCED INTUMESCENT FIRE RETARDANT COATING FOR STRUCTURAL APPLICATIONS - ,, HAMMAD AZIZ (2014)
Intumescent fire retardant coating (IFRC) is one of the easiest ways of protecting structural steel from fire. In present research work, IFRC was developed using ammonium polyphosphate (APP), expandable graphite (EG), melamine (MEL), boric acid (BA) and Bisphenol A BE-188 with polyamide amine H-2310 as curing agent. Three formulations were developed by varying the wt.% of ingredients and control formulation was determined based on best thermal insulation. Control formulation was further reinforced with titanium oxide (Ti02), magnesium oxide (MgO) and alumina (Ah03) as inorganic filler. Different formulations were developed by varying the wt. % of inorganic filler to study their effect towards char expansion, thermal insulation, char morphology, char composition and toxicity of gases. Furnace fire test was conducted at 500°C for 2 h to determine the physical appearance of char and intumescent factor. Bunsen burner test was conducted for 1h to study the thermal insulation of coating on structural steel substrate.